The growth of single-sex schools: Federal policy meets local needs and interests - Mansfield, Katherine Cumings (Education Policy Analysis Archives, 2013)
Changes to Title IX allowing the growth of single-sex schools have garnered media attention promoting the benefits of separating boys and girls. Alternately, civil rights groups such as the ACLU continue to oppose any type of school segregation. Within this context, a private philanthropy, the Foundation for the Education of Young Women (FEYW) has established public-private partnerships with six Texas school districts to open all-girls’ public college prep magnet schools with plans to expand. This multi-year ethno-historical case study explores the meaning making of one community in the FEYW network as it attempts to make sense of federal policy at the local level. The topic is important to the field of education because it is timely: changes to Title IX and the growth in single-sex arrangements pose interesting legal and sociological questions about equity and justice since it links Title IX (an equity-driven policy) with the choice provisions in NCLB (a market-driven policy). The significance of this study lies in the unique use of ethnography as interpretive policy analysis to show how local communities (re)interpret federal policy to better align with their personal values and more adequately address contextual complexities in their attempts to do what they believe is best for students.